Methods to Strengthen Research Competencies of Prospective Educators - Botirovna, Musoyeva Aziza; Abadi, Satria (Journal of Education Method and Learning Strategy, 2025)
Enhancing research skills in prospective teachers is essential for fostering reflective practice and contributing to the academic community. This study examines effective strategies for enhancing the research proficiency of pre-service teachers by emphasizing the integration of research into teacher training programs, leveraging technology, and facilitating collaborative inquiry. This study aims to assess potential instructors' academic writing proficiency and research competency. Utilizing Google Forms, an online survey instrument, 397 prospective educators were administered a revised multiple-choice questionnaire. The survey responses were statistically analyzed using the capabilities of Google Forms, facilitating descriptive statistics. The survey results indicate that a significant proportion of prospective educators possess knowledge of research skills and academic writing.